Counseling on Selecting Quality Universities According to Student Interests - Syahril; Dedi Julianto; Antaridha; Rahil Khairani (Journal of Community Service and Application of Science, 2025)
3rd grade high school students are still confused about choosing which state university they will enter as well as private universities both in Indonesia and in West Sumatra, especially SMA Negeri 1 Rao Pasaman Timur Sumbar and SMA Negeri 1 Muara Sipongi Mandailing Natal North Sumatra who are still confused about choosing a university with the right major according to their talents and interests. To eliminate their confusion, we, the lecturers of the Faculty of Economics, Dharma Andalas University, feel the need to provide guidance and counseling to them about choosing the right state or private university according to their talents later so that they do not get stressed in carrying out their studies later. Dharma Andalas University is the only private university under the guidance of UNAND alumni located in the center of Padang city which is easily accessible to students later. This is one of the advantages of Dharma Andalas University. This promotional activity was carried out at SMA Negeri 1 Rao Pasaman Timur West Sumatra and SMA Negeri 1 Muara Sipongi Mandailing Natal North Sumatra. This community service-based promotional activity was very helpful for the third-grade students who were visited. After being given guidance and counseling, they learned that the quality of higher education is largely determined by the accreditation of each study program. And featuring the study programs at Dharma Andalas University, which consists of 17 study programs, they were very enthusiastic about participating in this guidance and counseling event which was showered with various questions related to strategies for choosing a quality college according to their talents.